The metamorphosis in the paintings of Jean Dubuffet - Ali Ameen Sami, Lecturer Dr. (lark, 2022)
The research was divided into four chapters. The first chapter included a definition of the research problem, which was summarized by the following question: - What is the formal transformation in Jean Dubuffet's Paintings? And the importance of the research and the need for it, and the goal of the research, which was summarized by (knowing the formal transformation in the paintings of Jean Dubuffet). The first chapter also included a definition of the limits of the research, and defining the terms contained therein. As for the second chapter, which is the theoretical framework for the research, it has been divided into two sections: The first topic is concerned with (the concept of transformation in art). The second topic is concerned with (the figure in Dubuffet's paintings). It also includes indicators of the theoretical framework. The third chapter included the research procedures, from the research community, the research sample, the research tool, the research methodology, and the analysis of the research sample. The fourth chapter included the results of the research, and among the results reached by the researcher: Shape transformations appeared in Dubuffet’s work, loaded with stylistic values ​​aimed at breaking monotony and stagnation and searching for different expression mechanisms by discovering new aesthetic values ​​that are originally the result of intellectual transformations. The fourth chapter also included: - Recommendations, the most important of which is: Continuous updating of the curricula of fine arts studies, as there is no systematic book that talks about contemporary art, except for the effort made by the teaching staff.- The proposals, the most important of which is: the role of the material in the paintings of abstract expressionism. Then comes after the fourth chapter: index of sources.
Keywords: metamorphosis; paintings; Dubuffet; Abstract Expressionism; Art